Extension of mepolizumab injection intervals as potential of saving costs in well controlled patients with severe eosinophilic asthma - Georg Bölke, MD; Xunliang Tong, MD; Torsten Zuberbier, MD, PhD; Jean Bousquet, MD, PhD; Karl-Christian Bergmann, MD, PhD (World Allergy Organization Journal, 2022)
Background: Present guidelines recommend a life-long therapy with mepolizumab in patients suffering from severe eosinophilic asthma as several studies proved the disadvantages of treatment cessation. This study evaluated the possibility of extending the dosage intervals of mepolizumab in those patients with severe eosinophilic asthma after being well controlled. Methods: Eighteen patients diagnosed with severe eosinophilic asthma were started on treatment with mepolizumab in regular 4-week intervals. Symptom control was measured using the asthma control test (ACT) and pulmonary function test every 3 months. The amount of oral corticosteroids needed to maintain symptom control was monitored at every visit. After achieving good symptom control, defined as well controlled ACT ≥20, injection intervals were prolonged from 4 up to 6 to 8 weeks. The evaluation of this data was approved by the ethics committee. Results: ACT and pulmonary function values significantly improved after initiating therapy with mepolizumab on a regular 4-weekly injection interval. After extending the dosage intervals, both ACT and pulmonary function remained on a stable level without significant changes during the follow-up visits for 1 year. Median dosage of prednisolone declined significantly in the studied group under mepolizumab therapy and stayed on a low level during the follow-up visits with only a single patient using prednisolone after 1 year. Conclusion: In patients with fully or well controlled eosinophilic asthma treated with mepolizumab extending the dosage intervals between the injections up to 8 weeks bears the potential to save costs for the health care system.